Computer mediated communication: A motivational strategy toward diverse learning style - Rusnani Abdul Kadir; Rosseni Din (penerbit ukm, 2006)
This study define learning style as the way in which each learner begins to concentrate, process, and retain new and difficult information. It uses the Kolb’s Learning-Style Inventory (LSI) (1985), to assess the learning style of 241 students from two urban secondary schools in Malaysia. The finding of this study shows that secondary school children in Malaysia tend to use reflective observation in their learning mode orientation. This means that they are reflective information processors and they understand new situations through concrete perceptions. Teaching and learning in Malaysian secondary schools tend to be traditional and teacher centered. Students are not expected to be active information-seekers. Instead, they are presented with materials and given very limited space to deviate, what more to challenge the teachers and other people of authority. The learner with this orientation does a lot of watching and reflecting. Consequently, the learning styles of these students are of Diverges. Hence, the study suggested that computer mediated